Klasifikasi Emosi Putri Kaguya dalam Anime Kaguya-hime no Monogatari: Kajian Psikologi Sastra - I Putu Gede Parameswara; Ni Luh Gede Meilantari (Jurnal Bahasa Jepang Taiyou, 2023)
Kaguya-hime no Monogatari Anime is a 2013 animation film based on the Japanese folktale Taketori monogatari that was adapted by Studio Ghibli with a runtime of 2 hours and 17 minutes. The purpose of this research is to characterize the emotional categorization of Princess Kaguya, the main character of the anime Kaguya-hime no Monogatari, employs David Krech's Emotion Classification theory in Minderop (2018). This study is a descriptive qualitative study. Video analysis and note-taking procedures were used to obtain data. The data in this study comprises talks between characters and photos collected of an event or events in the novel, which are then examined using identification and categorization. The data analysis findings are given descriptively, together with images from the anime Kaguya-hime no Monogatari. The findings revealed that the seven emotional classes were discovered in the story's main character Princess Kaguya. These feelings are classified as follows: 2 conceptions of guilt, 1 pent-up guilt, 2 self-punishment, 1 shame, 12 sadness, 4 hatred, and 7 love.